2019
DOI: 10.1101/652669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The polymorphic PolyQ tail protein of the Mediator Complex, Med15, regulates variable response to stress

Abstract: The Mediator is a multi-protein complex composed of subunits called head, body, tail, and CDK that is conserved from yeast to humans and plays a central role in transcription. However, not all the components are required for basal transcription. Components of the tail are not essential but to varying degrees are required for growth in different stresses. While some stresses are familiar such as heat, desiccation, and starvation, others are exotic, yet yeast can elicit a successful stress response. MCHM is a hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…It has been proposed that the EP400 gene plays a significant role in oligodendrocyte survival and myelination in the vertebrate central nervous system (11). A study proposed that Gene MED15 polyglutamine repeat length changes the expression of diverse stress pathways (12). Among various populations, it has been reported that CAG repeat variation in MEF2A is a risk factor for coronary artery disease (CAD) (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the EP400 gene plays a significant role in oligodendrocyte survival and myelination in the vertebrate central nervous system (11). A study proposed that Gene MED15 polyglutamine repeat length changes the expression of diverse stress pathways (12). Among various populations, it has been reported that CAG repeat variation in MEF2A is a risk factor for coronary artery disease (CAD) (13).…”
Section: Discussionmentioning
confidence: 99%